The evolution of knowledge : rethinking science for the Anthropocene - Renn, Jürgen (Princeton University Press, 2020)
Klappentext: This book presents a new way of thinking about the history of science and technology, one that offers a grand narrative of human history in which knowledge serves as a critical factor of cultural evolution. Jurgen Renn examines the role of knowledge in global transformations going back to the dawn of civilization while providing vital perspectives on the complex challenges confronting us today in the Anthropocene-this new geological epoch shaped by humankind. Renn reframes the history of science and technology within a much broader history of knowledge, analyzing key episodes such as the evolution of writing, the emergence of science in the ancient world, the Scientific Revolution of early modernity, the globalization of knowledge, industrialization, and the profound transformations wrought by modern science. He investigates the evolution of knowledge using an array of disciplines and methods, from cognitive science and experimental psychology to earth science and evolutionary biology. The result is an entirely new framework for understanding structural changes in systems of knowledge-and a bold new approach to the history and philosophy of science. Written by one of today's preeminent historians of science, The Evolution of Knowledge features discussions of historiographical themes, a glossary of key terms, and practical insights on global issues ranging from climate change to digital capitalism. This incisive book also serves as an invaluable introduction to the history of knowledge.